PROBLEMS AND SOLUTIONS TO THE QUALITY OF THE GINING PROCESS IN UZBEKISTAN - Abdullayev, Ravshan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: Saw gin's problems in separating fibers from seeds have been identified through extensive research and laboratory testing. First of all, the natural properties of six selected varieties of cotton fiber were determined and studied using modern complex laboratory equipment HVI-900 SA.